Colonial education and industrialization - LU, Wenyuan (KDI School, 2023)
This study examines how colonial education affects industrialization in the context of Korea under Japanese rule. I focus on the role of the two different languages, Japanese and Korean. Rising literacy rates of Korean and Japanese would reflect improving cognitive abilities and better chances of adopting advanced technologies, respectively. Collecting and examining district-level data, I test how each channel contributed to the industrialization of colonial Korea. I find that having a Japanese literacy rate is strongly associated with the development of non-agricultural industries in 1930. In contrast, the Korean literacy rate does not show a significant correlation. This means that knowing the colonial language gave an advantage to learning new technology and entering a new sector. I also address potential endogeneity by instrumenting the Japanese literacy rate by the presence of civil exam passers during the Joseon Dynasty, which corroborates my results. My study sheds light on the role of colonial education in the industrialization of latecomer countries.
Thesis(Master) -- KDI School: Master of Devemopment Policy, 2023
Keywords: Education--Korea--Japanese occupation, 1910-1945; Bilingualism--Korea--Japanese occupation, 1910-1945